Case report: Magnetic resonance imaging features with postoperative improvement of atypical cervical glioma characterized by predominant extramedullary distribution in a dog - Kim, Junyoung; Kim, Kihoon; Chung, Dai Jung; Kim, Yebeen; Kim, Kitae; Oh, Dayoung; Lee, Namsoon; Choi, Jihye; Yoon, Junghee (Frontiers in Veterinary Science, 2024)
Introduction: Intramedullary cord tumors present diagnostic and therapeutic challenges. Furthermore, spinal cord tumors can move across compartments, making antemortem diagnosis difficult, even with advanced imaging. This report presents a rare case of a cranial cervical spinal glioma, confirmed by surgical histopathology, with postoperative improvement in a dog. Case description: A 9-year-old female Maltese dog presented with kyphotic posture, progressive left hemiparesis, and decreased appetite. Neurological examination revealed neck pain and decreased proprioception in the left limbs along with intact deep pain perception. Two days later, the patient developed non-ambulatory tetraparesis. Magnetic resonance imaging (MRI) revealed an ovoid, welldefined mass with homogeneously marked contrast enhancement in the second cervical spinal cord that severely compressed the spinal cord. This mass was heterogeneously hyperintense on T2weighted images and iso-to-hypointense on T1-weighted images, showing an appearance resembling the "golf-tee" and "dural tail" signs. The MRI findings suggested an intradural extramedullary tumor. Intraoperatively, a well-demarcated mass which was locally adherent to the spinal meninges was removed. Both histopathological and genomic tumor tests were indicative of a glioma. Approximately 2 weeks postoperatively, the patient's neurological signs returned to normal. Conclusion: This case report describes an atypical cervical glioma with complicated MR characteristics in a dog, where MRI helped guide surgical intervention.